2002
DOI: 10.1071/ea02019
|View full text |Cite
|
Sign up to set email alerts
|

Modelling crop growth and yield under the environmental changes induced by windbreaks 1. Model development and validation

Abstract: Yield advantages of crops grown behind windbreaks have often been reported, but underlying principles responsible for such changes and their long-term consequences on crop productivity and hence farm income have rarely been quantified. Physiologically and physically sound simulation models could help to achieve this quantification. Hence, the APSIM systems model, which is based on physiological principles such as transpiration efficiency and radiation use efficiency (termed here APSIMTE), and the Soil Canopy A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Three windbreaks of different porosities (β) were created using different density meshes. [The general symbol for porosity is β: β O for optical porosity and β A for porosity determined using wind speeds measured upwind and in the bleed flow; β is used throughout this paper to refer to the porosity of the model windbreaks used in the wind tunnel and should not be confused with the same symbol used in Meinke et al (2002) which is a calibration factor. ]…”
Section: Overview Of Wind-tunnel Experimental Methodsmentioning
confidence: 99%
“…Three windbreaks of different porosities (β) were created using different density meshes. [The general symbol for porosity is β: β O for optical porosity and β A for porosity determined using wind speeds measured upwind and in the bleed flow; β is used throughout this paper to refer to the porosity of the model windbreaks used in the wind tunnel and should not be confused with the same symbol used in Meinke et al (2002) which is a calibration factor. ]…”
Section: Overview Of Wind-tunnel Experimental Methodsmentioning
confidence: 99%
“…The APSIM model was adapted to predict the effects of wind shelter on crop yields. Validation of this modelling approach was limited to the measured results from the artificial shelter sites as none of the field studies found an unequivocal yield response to shelter (Meinke et al 2002;Carberry et al 2001). Hence, there is some uncertainty in the model's validity.…”
Section: Are Windbreaks Profitable? Results From Apsim Simulationsmentioning
confidence: 99%
“…Crop growth simulations using APSIM. The philosophy and architecture of APSIM (Agricultural Production Systems Simulator) are detailed in Meinke et al (2002). APSIM was used to predict crop growth and final yields for the field sites (Esperance barley, Roseworthy wheat, Atherton maize) and artificial shelters (Esperance wheat, Rutherglen wheat and Warwick wheat and mung bean).…”
Section: Modellingmentioning
confidence: 99%
“…APSIM setup APSIM (version 1.54), using crop modules for maize, mungbean and wheat, was used to predict the growth, development and yield of maize, mungbean and wheat crops grown at the sites nominated in Table 1. Meinke et al (2002) described in detail how APSIM was specified to simulate crop performance behind windbreaks. Briefly, the following assumptions were employed: (i) As APSIM crop modules have been developed and tested around Australia using a transpiration efficiency (TE) approach to determine daily transpiration demand (Carberry et al 1996;Meinke et al 1998), crop yields simulated at each site using this approach (APSIM TE ) were regarded as 'baseline yields' for the purposes of this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In the first paper in this series, Meinke et al (2002) described how the cropping systems model, APSIM (Agricultural Production Systems Simulator) (McCown et al 1996), was specified to simulate crop growth under the environmental changes induced by windbreaks. APSIM simulation of potential evapotranspiration and crop growth under altered wind speed conditions was respectively tested against predictions from the SCAM micrometeorological model (Raupach et al 1997) and limited crop data from artificial shelter experiments .…”
Section: Introductionmentioning
confidence: 99%